Comisión de Enseñanza de Posgrado Informe 6 - Adrover, Jorge; Ateca, María Rosa; Baruzzi, Ana María; Berti, Agustín; Castro, Alejandra María; Corral Briones, Graciela; Dalmasso, Eduardo; Guzmán, Claudia; Kisbye, Noemí Patricia; Lescano De Ferrer, Alfonsina; Spadiliero De Lutri, Mirta; Valentich, Mirta (Universidad Nacional de Córdoba, 2018)
Fil: Adrover, Jorge. Universidad Nacional de Córdoba; Argentina.